Properties of particulate pollution in the port city of Valparaiso, Chile. (December 2017) - Marín, Julio C.; Raga, Graciela B.; Arévalo, Jorge; Baumgardner, Darrel; Córdova, Ana M.; Pozo, Diana; Calvo, Ana; Castro, Amaya; Fraile, Roberto; Sorribas, Mar
Abstract: The city of Valparaiso is home to one of the largest commercial ports on the west coast of South America. Port activities, that continue year-round, 24 h a day and seven days a week, produce emissions of pollutants, particularly aerosol particles composed of black and brown carbon (BC and BrC) that have serious impact on human population and the local environment. A measurement program was launched to document the magnitude of selected pollutants, to identify their sources and to evaluate the meteorological processes that enhance and transport these pollutants locally and regionally. In this study, we report the measurements made during four months: 25July - 25August 2014 (referred to as August 2014 throughout the manuscript), December 2014, January 2015 and March 2015. The daily mass concentrations of equivalent black carbon (eBC), derived from measurements of the light absorption coefficient, regularly exceed 5 μg m −3, a magnitude similar to values found in megacities such as Mexico City. The daily maximum number concentration of condensation nuclei (CN) is usually larger than 30000 cm −3 . The Angstrom absorption exponent (AAE), derived from the absorption coefficients at 550 nm and 870 nm, is used to identify the primary sources of BC and BrC. In colder weather, emissions from the diesel fueled buses and trucks and the consumption of kerosene and wood for residential heating are the main sources of BC. In December, local wildfires contributed to the particle mass loading, but the day-to-day variability in boundary layer height and the presence of clouds and fog in occasions inhibited high concentrations. In March, the port activities reach a yearly peak during the seasonal export of agricultural products that translates into much more ship and truck traffic leading to very high eBC concentrations, comparable to values observed during August. The variability in weather patterns underscores the complexity of meteorological processes that drive the evolution and transport of pollution in Valparaiso. Highlights: Primary emission sources: local vehicular traffic, port activities, residential heating and wildfires, all depend on meteorology and season. Residential wood burning and urban transport emissions and low PBL and winds lead to largest concentrations of eBC and CN in August. Second largest concentrations observed in March, with high PBL and strong winds due to increased port activities (ships and trucks) of agricultural exports. Maximum eBC, PPAH and CN concentrations often approached magnitudes observed in Mexico City, with much higher population than Valparaiso.